Ecowarriors Bring Back Kumandra: An Ecofeminism Study Depicted in Raya and the Last Dragon - Irma Imroatina; Ari Setyorini; Pramudana Ihsan (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
This research discusses the study of ecofeminism found in the Raya and the Last Dragon movie. This research's objective was to reveal how the ecofeminist figures (Raya, Sisu, and Namaari) save their homeland called Kumandra. The ability of women to take care of nature is considered an important role. The attitude of mothering spirit, nurturing, and caring qualities are essential to keeping nature safe. Women have the energy to do the protest against environmental damage. The attitude of raising and caring for nature can also be brought in literary works with the study of ecofeminism. This research uses a descriptive qualitative method. The research data took from the storylines and dialogue in Raya and the Last Dragon movie. As a result, the ecowarriors have a meeting point by flocking and working together to achieve the same vision and mission to save Kumandra from Druun by uniting and trusting each other.This research discusses the study of ecofeminism found in the Raya and the Last Dragon movie. This research's objective was to reveal how the ecofeminist figures (Raya, Sisu, and Namaari) save their homeland called Kumandra. The ability of women to take care of nature is considered an important role. The attitude of mothering spirit, nurturing, and caring qualities are essential to keeping nature safe. Women have the energy to do the protest against environmental damage. The attitude of raising and caring for nature can also be brought in literary works with the study of ecofeminism. This research uses a descriptive qualitative method. The research data took from the storylines and dialogue in Raya and the Last Dragon movie. As a result, the ecowarriors have a meeting point by flocking and working together to achieve the same vision and mission to save Kumandra from Druun by uniting and trusting each other.